(3QSGdI aj Hjf hHjfG hHjfeGs - (3GdeZfjSGhj , CMeO Hf eMeO,J (B1090 (3g` s
(3ChdgG (B:s
(3CeG HYO, ceG QCjJ daXI Hjf eJOGhdI Hjf GdCfGe hcKjQI GdhQhO aj GdcdGe, aWGdYJ aj Pdc GdbGehS s
(3BNQgG (B:s
(3GdKGdK(B: (3Cf eG RGFOI, hHjf eVGaI Edi GdLed faSgG, aGdLedI aj eMd LqQ GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B159 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B162s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B133 s
Keywords: (3GdfMhs